2019
DOI: 10.1016/j.cell.2018.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Late Endosomes Act as mRNA Translation Platforms and Sustain Mitochondria in Axons

Abstract: SummaryLocal translation regulates the axonal proteome, playing an important role in neuronal wiring and axon maintenance. How axonal mRNAs are localized to specific subcellular sites for translation, however, is not understood. Here we report that RNA granules associate with endosomes along the axons of retinal ganglion cells. RNA-bearing Rab7a late endosomes also associate with ribosomes, and real-time translation imaging reveals that they are sites of local protein synthesis. We show that RNA-bearing late e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
417
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(436 citation statements)
references
References 69 publications
(97 reference statements)
17
417
1
1
Order By: Relevance
“…S2e) 2Btubwt transport complexes was 0.57 m/s ( Fig. 2d) which matches the reported velocity for KIF3ABK in cells 25 and in vitro 26 and also the reported velocities for axonally localised RNAs in cultured neurons 9,27 . and a C-terminally localised Tau-like microtubule binding site 30 , could function as recruitment factor for KIF3ABK.…”
Section: Resultssupporting
confidence: 88%
“…S2e) 2Btubwt transport complexes was 0.57 m/s ( Fig. 2d) which matches the reported velocity for KIF3ABK in cells 25 and in vitro 26 and also the reported velocities for axonally localised RNAs in cultured neurons 9,27 . and a C-terminally localised Tau-like microtubule binding site 30 , could function as recruitment factor for KIF3ABK.…”
Section: Resultssupporting
confidence: 88%
“…Although it has been well-established that local translation occurs in axons and growth cones, we do not know where this translation occurs within these neuronal compartments. One recent study demonstrated that late endosomes are a platform for local translation within axons (38). Here we add to our knowledge about platforms for local translation by demonstrating that local translation also occurs at point contacts.…”
Section: Point Contacts Are Sites Of Local Translation In Growth Conessupporting
confidence: 52%
“…The cell body is also the site of the majority of protein synthesis in neurons. While mRNA and protein transport from the cell body to organelles in the axon can contribute to the replenishment of mitochondrial proteins 13 , it stands to reason that moving the organelle back to the primary site of protein synthesis is an efficient mechanism for bulk mitochondrial protein turnover. Our proteomics data support this as mitochondria isolated from mutants that lack mitochondrial retrograde transport show a substantial reduction in approximately a third of their mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria, Axonal Transport, Cytoplasmic dynein, Mitochondrial protein import, Retrograde transport, Dynactin, Actr10, p150 glued regulation of local translation 13,14 . Therefore, maintaining a healthy pool of mitochondria, particularly in distal compartments of the neuron, is critical for the health and maintenance of functional neural circuits.…”
Section: Introductionmentioning
confidence: 99%